El De arte combinatoria de G.W. Leibniz como una teoría de la ciencia - Correia, Manuel (2014)
The article presents the theory of variations in G.W. Leibniz’s De arte combinatoria as a theory of science. Their relation is suggested by the text in terms of that human reason can jus- tify the validity of all the propositions belonging to empirical sciences that have been acquired by single observations or by an observation plus a universal law. Human reason finds through the analysis the way in which the variety of things are related among them. This allows that reason completes deductively the system of sciences by a combinatorial synthesis whose laws are the laws of inventive logic which is founded on the princi- ples of combinatory and arithmetic.